Diseño, Aplicación Y Evaluación De Un Ambiente Virtual De Aprendizaje Aplicando Google Apps - Arturo, González Torres; Edgardo, Díaz Colín; Azucena, Flores Arroyo; Erik G, Alejaldre Martínez; Suriel, Yescas Hernandez; Cristian, Aguilar Zamudio (European Scientific Journal, ESJ, 2016)
.